FREEDOM OF ISLAMIC EXPRESSION IN MALAYSIA - Mohd Azizuddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2017)
In Malaysia, Islam is the religion of the Federation, and the Islamic law system runs parallel to the civil law system. This triggers a political debate in defining Malaysia as either an Islamic or a secular state which makes the non-Muslims uneasy. Malaysia is also a multi-religious society prone to inter-group conflict. As such, care is taken not to publish articles that cast a slur on any religions in the country. Some of the contentious issues imposed in the press such as the case of the word ‘Allah’ and blasphemy and dissent against religious authority. Although the purposes of restriction are for political stability and national security, the ruling government has indeed manipulated the religious expression for political domination and regime security.